Exploring cultural and creative product design through determining the significance characteristics of hongshan pottery pattern / Lin Lin, Prof. Madya Dr. Nur Hisham Ibrahim and Dr. Neesa Ameera Mohamed Salim - Lin, Lin; Ibrahim, Nur Hisham; Mohamed Salim, Neesa Ameera (Universiti Teknologi MARA, Kedah, 2025)
Hongshan Culture is one of China's precious cultural heritages and is among the most renowned archaeological cultures of the Neolithic era in Northeast China. Among the unearthed artifacts from the Hongshan Culture, pottery stands out as a typical item, offering insights into the aesthetic views, primitive religious beliefs, and cultural characteristics of the Hongshan Culture period. This holds significant academic value. In comparison to theoretical achievements in studying Hongshan Culture patterns, research on creative product design inspired by Hongshan Culture is relatively scarce. The primary aim of this study is to identify the significance characteristics of Hongshan Culture pottery patterns, thereby sparking reflections on incorporating these unique and typical patterns into creative product design. Through expert interviews, this research comprehensively explores seven aspects of Hongshan Culture pottery patterns: cultural significance, totem worship, religious beliefs, philosophy significance, auspicious significance, significant characteristics patterns, and their application in cultural and creative product design. The study ultimately defines the significance characteristics of Hongshan Culture pottery patterns and provides design suggestions for integrating these classic patterns into creative product designs.